Application of barley flour processed by different methods as an alternative to fat in emulsion‐type sausage. Issue 1 (27th March 2022) - Zhu, Ying; Huang, Shiting; Jia, Donghao; Zhao, Yansheng; Zhang, Jiayan; Bai, Juan; Xiao, Xiang
Abstract: Physicochemical properties of three types of barley flour, whole barley flour (BF), electromagnetic stir‐frying whole barley flour, and extruded whole barley powder (EBF), and their potential application in emulsion type sausage were evaluated in this study. The water solubility index, water absorption index, and pasting properties of barley flour treated by different processing technologies were significantly different. The EBF has the highest water solubility index (12.67%) and water absorption index (503.20%), and with the minimum peak viscosity (2593.67 cp) and pasting temperature (50.20°C). The water‐holding capacity and cooking loss of emulsified sausage improved significantly after adding the barley flour processed by different methods, especially the 9%BF substitution, the pressure water loss rate and cooking loss rate were reduced to 5.32% and 14.52%, respectively. The emulsified sausage added with BF indicated better color quality and texture properties comparable with the control. Scanning electron microscopy also showed that the addition of three kinds of barley flour in sausage formation led to a difference in the microstructure of the sausages. This study suggested that barley flour improved the physicochemical and textural properties of the emulsified sausage. Abstract : Three types of barley flour were prepared. The emulsion‐type sausages added with barley flour processed by different methods had different water‐holding capacity, cooking loss, texture profile analysis, color, and microstructure.